HEPATOPROTECTIVE ACTIVITY OF AQUEOUS EXTRACT OF OXALIS DEBILIS KUNTH AGAINST CCL4 - INDUCED LIVER DAMAGE - Athokpam, Rojini; Bawari, Meenakshi; Choudhury, Manabendra Dutta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: To evaluate the hepatoprotective activity of aqueous extract of Oxalis debilis Kunth in carbon tetrachloride (CCl4)-induced hepatotoxicity in Swiss albino mice. Methods: Hepatotoxicity was induced by CCl4 30% in olive oil (1 ml/kg intraperitoneally). Mice were treated with aqueous extract of O. debilis at doses of 250 and 500 mg/kg body weight orally for 14 days. There were two groups, pre-treatment (once daily for 14 days before CCl4 intoxication) and post-treatment (2, 6, 24, and 48 hrs after CCl4 intoxication). The observed effects were compared with a known hepatoprotective agent, silymarin. Results: Pre-treatment and post-treatment groups of aqueous extract of O. debilis significantly reduced elevated serum levels of serum transaminases, alkaline phosphatase, and bilirubin and increased the level of total protein as compared to CCl4-treated group. The histopathological study also confirms the hepatoprotection. Preliminary qualitative phytochemical analysis of the plant revealed the presence of phenolic compounds, tannins, flavonoids, and saponins. Conclusion: The results of this study suggest that O. debilis can be used as safe, cheap, and alternative preventive and protective drugs against liver injury. The protective effect observed could be attributed to the presence of various phytochemicals which are responsible for the restoration of liver damage.